Ozone: A Review of Recent Experimental, Clinical and Epidemiological Evidence, with Notes on Causation—Part 1 - David V Bates (Canadian Respiratory Journal)
Part 1 of this review is concerned with theoretical issues of ozone dosimetry, animal and cellular studies that illustrate the mechanism of action of ozone on living tissues, and with clinical studies. Animal studies have indicated that there are long term effects from low level long term ozone exposure. Clinical studies involve controlled ozone exposures on human subjects, both normals and asthmatics. Exercise concomitant with the ozone exposure increases the effect of the gas. It is concluded that the induction of an inflammatory response in the airway, both in the nose and in the lung, is the striking and earliest feature of ozone exposure. Current unexplained observations include: the dissociation between the inflammatory and function test response; the mechanisms of ‘adaptation’ and of airway hyperresponsiveness; and the phenomena that underlie the effect of ozone on maximal athletic performance.